Effect of ozone treatment on the reduction of chlorpyrifos residues in fresh lychee fruits - Whangchai K. (2014)
The effect of ozone on the reduction of chlorpyrifos residue in lychee cv. Chakapat (Litchi chinensis Sonn.) was studied. Lychee fruits were dipped in the solution of chlorpyrifos at a concentration of 10 mg L-1 for 10 min. Then, they were exposed to ozone gas (O3) at concentrations of 80, 160, 200, 240 mg L-1 and dipped in ozone- containing water, at concentrations of 2.2, 2.4, 3.4 and 3.2 mg. L-1 for 10, 20, 30 and 60 min, respectively. Both ozone gas and ozone-containing water reduced pesticide residue in lychee, but exposure to ozone gas for 60 min was most effective. When lychee fruits were stored at 25°C for 6 days, both processes did not show significant differences in weight loss, total soluble solids (TSS) and titratable acidity (TA). However, ozone-containing water decreased the eating quality of lychees after storage, compared with the ozone-fumigated groups. © 2011 International Ozone Association.